Partial caries removal in deep lesions: 19-30 months follow-up study - Marisa Maltz; Mauricio Moura; Juliana Jobim Jardim; Cyntia Marques; Lilian Marly de Paula; Heliana Dantas Mestrinho (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2010)
The aim of this multicenter randomized controlled clinical trial was to evaluate the effectiveness of partial caries removal followed by restoration in a single session (PDR) for deep caries lesions in Brazil (Porto Alegre and Brasilia) after 2-year follow-up. Inclusion criteria: patients with ≥ six years old presenting permanent molars with primary deep lesion, absence of periapical alterations, pulp sensitivity, absence of spontaneous pain and negative percussion test. The subjects were randomly assigned to test group - PDR, or control group - stepwise excavation (SW). SW consisted of partial removal of carious dentine, indirect pulp capping with calcium hydroxide cement, temporary filling, cavity re-opening after 60 days, removal of the remaining soft carious dentine and filling. Each group was divided according to the filling material: amalgam or resin. Clinical and radiographic evaluations were performed in annual basis. The outcomes were considered as pulp sensibility to cold test and absence of periapical alterations. There were performed 299 treatments, 153 PDR and 146 SW. There were no differences between the groups regarding baseline characteristics. After 2 years of follow-up, 204 restorations were evaluated and the therapy survival rates of PDR and SW were 95.45% and 80.85%, respectively (p=0.001). Reasons for failure: pulpitis, osteitis, hyperemia, necrosis, extraction and restoration fracture.. None variable was significantly associated with the outcome. From these results, it is possible to conclude that the PDR is a more successful treatment than SW. (Registration number at www.clinicaltrials.gov NCT00887952).